Males Experiencing Childhood Sexual Abuse and Their Associations with Psychological Distress - (:unkn) unknown (My University, 2013)
Childhood sexual abuse (CSA) is an important issue relatively recently beginning to gain attention from professionals. Studies show that males are underrepresented in the literature, although CSA is a prevalent problem for males as well as females. This study was developed to add to the existing literature on males and CSA, obtain prevalence rates from a nationally representative, epidemiological study, and find correlates between CSA and psychological distress factors. The epidemiological study used was the National Comorbidity Study-Replication (NCS-R). This was a large survey of U.S. households investigating correlates and comorbidities of psychological disorders. Secondary analyses were completed on the NCS-R including prevalence rates of CSA in men compared to women, racial/ethnic information of men, associations with psychopathology as a function of CSA history in men, and demographical differences. It was found that there is indeed a significant difference between men with and without a history of CSA on race/ethnicity, socio-economic issues, psychological disorders, substance use, suicidality, use of mental health services, and experiencing other traumatic events, especially those involving interpersonal violence. Implications include support for increased use of screening for CSA within professional services that men with CSA have increased use of, including mental health and substance abuse services.
Keywords: Abuse; Childhood Sexual Abuse; Distress; Males; Pathology